Academic Emotions Affected by Robot Eye Color: An Investigation of Manipulability and Individual-Adaptability - Koike, Kento; Tsuji, Yuya; Tomoto, Takahito; Katagami, Daisuke; Obo, Takenori; Ogai, Yuta; Sone, Junji; Udagawa, Yoshihisa (International journal of advanced computer science & applications, 2019)
We investigate whether academic emotions are affected by the color of a robot’s eyes in lecture behaviors. In conventional human-robot interaction research on robot lecturers, the emphasis has been on robots assisting or replacing human lecturers. We expanded these ideas and examined whether robots could lecture using one’s behaviors that are impossible for humans. Psychological research has shown that color affects emotions. Because emotion is strongly related to learning, and a framework of emotion control is required. Thus, we considered whether emotions related to the learner’s academic work, called “academic emotions,” can be controlled by the color of a robot’s illuminated eye light. In this paper, we found that the robot’s eye light color affects academic emotions and that the effect can be manipulated and adapted to individuals. Furthermore, the manipulability of academic emotions by color was confirmed in a situation mimicking a real lecture.